2014
DOI: 10.1007/s12262-014-1110-x
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Duplication of the Sigmoid Colon with Acute Abdomen: An Adult Case Report

Abstract: Colonic duplication is a rare abnormality, comprising only 6-7 % of all gastrointestinal duplications and usually present during the first decade of life. Tubular duplications of the sigmoid colon are extremely rare and only a few cases have been reported in the literature. In this study, we report the case of a 27-year-old rural man visited our hospital with symptom of repeated episodes of abdominal pain in epigastric region that radiated to right flank and back. An abdominal computed tomography (CT) scan wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…In this particular case, the diagnosis of colonic duplication was in the differential diagnosis, along with a giant diverticulum, volvulus and duplication cyst. Finally, in 2015, Sobhani et al 11 reported a case of a 27-year-old man who was diagnosed with a tubular sigmoid duplication intraoperatively after he had an exploratory laparotomy for an acute abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…In this particular case, the diagnosis of colonic duplication was in the differential diagnosis, along with a giant diverticulum, volvulus and duplication cyst. Finally, in 2015, Sobhani et al 11 reported a case of a 27-year-old man who was diagnosed with a tubular sigmoid duplication intraoperatively after he had an exploratory laparotomy for an acute abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic duplication is the most common type; only 20% of colonic duplications are tubular[ 11 ], which can be further divided into T- and Y-shaped duplications[ 12 ]. Tubular colonic duplication usually shares a common wall or has a direct communication with the native tract, as in our patient, unlike a cystic duplication[ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 86%
“…Abdominal CT is another necessary examination for duplication, which might reveal a low-density cystic structure or dilated lumen running parallel to the native tract[ 22 , 23 ]. Sobhani et al[ 2 ] reported a patient in whom the abdominal CT showed an extremely dilated and air-filled loop of bowel adjacent to the sigmoid colon; colonic duplication was later diagnosed intra-operatively. In our patient, two enlarged intestinal loops running parallel from the splenic flexure to the sigmoid colon were demonstrated, and the diagnosis was confirmed during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical variations of GI duplications include cystic (80%) and tubular (20%) types. Tubular type presents Y and T-shaped types 4–6. Cystic duplications often have no communication with native bowel whereas tubular malformations usually have direct communication or can share common bowel wall.…”
Section: Discussionmentioning
confidence: 99%